GLIMPSE: An ultrafaint ≃105 M⊙ pop III galaxy candidate and first constraints on the pop III UV luminosity function at z ≃ 6-7 - Fujimoto, Seiji; Naidu, Rohan P.; Chisholm, John; Atek, Hakim; Endsley, Ryan; Kokorev, Vasily; Furtak, Lukas J.; Pan, Richard; Liu, Boyuan; Bromm, Volker; Venditti, Alessandra; Visbal, Eli; et al. (The astrophysical journal, 2025)
Detecting the first generation of stars, Population III (Pop III), has been a long-standing goal in astrophysics, yet they remain elusive even in the JWST era. Here we present a novel NIRCam-based selection method for Pop III galaxies, and carefully validate it through completeness and contamination simulations. We systematically search ≃ 500 arcmin2 across JWST legacy fields for Pop III candidates, including GLIMPSE, which, assisted by gravitational lensing, has produced JWST’s deepest NIRCam imaging thus far. We discover one promising Pop III galaxy candidate (GLIMPSE-16043) at , a moderately lensed galaxy () with an intrinsic UV magnitude of . It exhibits key Pop III features: strong Hα emission (rest-frame EW 2810 ± 550 Å); a Balmer jump; no dust (UV slope β = −2.34 ± 0.36); and undetectable metal lines (e.g., [O iii]; [O iii]/Hβ < 0.44), implying a gas-phase metallicity of Zgas/Z⊙ < 0.5%. These properties indicate the presence of a nascent, metal-deficient young stellar population (<5 Myr) with a stellar mass of ≃105 M⊙. Intriguingly, this source deviates significantly from the extrapolated UV-metallicity relation derived from recent JWST observations at z = 4-10, consistent with UV enhancement by a top-heavy Pop III initial mass function or the presence of an extremely metal-poor active galactic nucleus. We also derive the first observational constraints on the Pop III UV luminosity function at z ≃ 6-7. The volume density of GLIMPSE-16043 (≈10−4 cMpc−3) is in excellent agreement with theoretical predictions, independently reinforcing its plausibility. This study demonstrates the power of our novel NIRCam method to finally reveal distant galaxies even more pristine than the Milky Way’s most metal-poor satellites, thereby promising to bring us closer to the first generation of stars than we have ever been before.
Im Titel ist M⊙ als Abkürzung für die astronomische Maßeinheit Sonnenmasse dargestellt
Gesehen am 08.01.2026